2022
DOI: 10.1097/hjh.0000000000003076
|View full text |Cite
|
Sign up to set email alerts
|

Aortic diastolic pressure decay explains sex-related differences in the subendocardial viability ratio: the Wakuya study

Abstract: Objective:Coronary heart disease is the leading cause of mortality in women. Despite a higher risk of heart failure after the first myocardial infarction in women compared with men, the sex-specific mechanisms are unknown. We hypothesized that myocardial ischemia is attributable to sex-related diastolic alterations in the central hemodynamics.Methods:We investigated the subendocardial viability ratio (myocardial oxygen supply/demand) and aortic diastolic pressure decay index in 962 apparently healthy adults (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…We thank Picone et al [1] for their interest in our recent article [2]. In our recent article, we demonstrated that aortic diastolic pressure decay is accelerated in women and mediates the relationship between sex and subendocardial viability ratio (SEVR).…”
mentioning
confidence: 88%
“…We thank Picone et al [1] for their interest in our recent article [2]. In our recent article, we demonstrated that aortic diastolic pressure decay is accelerated in women and mediates the relationship between sex and subendocardial viability ratio (SEVR).…”
mentioning
confidence: 88%
“…Other conventional pulse wave analysis variables that exhibit sex differences include sub-endocardial viability ratio and aortic diastolic decay index [86]. Sub-endocardial viability ratio provides an estimate of the ratio between myocardial oxygen supply and demand [87] and, when derived from carotid or estimated aortic pressure waveforms, is lower in women compared with men across different ages [88,89].…”
Section: Pressure and Flow Waveform Physiologymentioning
confidence: 99%
“…To our knowledge, there is no data on whether this contributes to sex differences in future CVD or predisposition to coronary heart disease. Thus, the clinical observations by Tagawa et al [19] should be interpreted with these caveats in mind. As the authors highlighted in their article, future studies should look to enrol patients with coronary disease and be performed longitudinally to determine causation.…”
mentioning
confidence: 95%
“…Suboptimal SEVR may create a supply–demand imbalance and limit favourable cardiac function. In this issue of the Journal of Hypertension , Tagawa et al [19] hypothesized that the sex difference in SEVR may be mediated by differences in diastolic pressure decay.…”
mentioning
confidence: 99%
See 1 more Smart Citation